An Overall Effective Tax Rate for The Romanian Companies Listed on The Regulated Market of The Bucharest Stock Exchange - Costel Istrate (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- How could we better measure the total tax burden of Romanian listed companies, what was its evolution what factors may influence it. Motivation- In many cases, the accounting literature limit the analyse of the tax burden to the corporate income tax. There are some effective tax rates (ETR) calculated on this basis; the major advantage of these ETRs is the comparability with the statutory tax rates which allows the identification of possible tax avoidance However, the tax burden of the companies include many other taxes and a complete figure of the fiscal efforts of these companies must consider all the taxes expensed and/or paid by the companies. There are studies and reports trying to address this problem, by including the labour taxes/contributions and other taxes. Idea- This paper extends the literature on the tax burden, taking into account not only the taxes directly expensed by the companies, but also the labour taxes/contributions paid in the name of their employees; thus, I propose an overall effective tax rate (OETR), as a ratio of this total tax burden to sales/revenues. Data- The data were collected from Romanian listed companies for 2001-2020 period; 1,377 observations are available. Tools- The study is descriptive: the OETR is calculated by sub-period, according to the financial reporting standards applied; I also provide the separation of the total tax burden intro three components: corporate income tax, labour taxes, other taxes. The evolution of the OETR is analysed by taking into account the size of the companies, the structure of the assets, the leverage, the profitability and the auditor category. Findings- On average, the most important component of the tax burden of Romanian listed companies is labour taxes/contributions. Despite a steady decrease in nominal tax rates, especially for labour contributions, the OETR has increased systematically over the period. The OETR is more important for small companies, for firms reporting more fixed assets, less leveraged, and audited by local auditors. Contribution- This research contributes to the fiscal research by examining the evolution of the total tax burden of Romanian listed companies in relation with some financial and non-financial variables.
Keywords: H20; M41; 650; overall effective tax rate; total tax burden; Romanian listed companies; labour taxes